Discussing the Phenomenon of the Appointment of Judges in District Courts Regarding Interfaith Marriages from a Legal Logic Perspective - Gemilang, Kemas Muhammad; Firmanda, Hengki; Maghfirah, Maghfirah; Lastfitriani, Hellen; Hakimi, Abdul Rahim (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This research aims to determine the intent of legislation and the constitution regarding interfaith marriages in Indonesia, so that judges can have a deeper understanding of the existing legal intent rather than relying solely on subjective legal interpretations. Additionally, this study also examines the authority of judges in District Courts who play a role in the determination of interfaith marriages. This research is a qualitative-normative study that utilizes legal documents and literature review, including books, journals, reports, and other reliable sources, which are analyzed using legal logic reasoning. Based on the researcher’s findings, legal logic reasoning in interpreting legislation indicates that interfaith marriages are prohibited. This can be seen in the constitutional goals of Indonesia in the fourth paragraph of the 1945 Constitution, the Judiciary Power Law in Article 5 and Article 50. The constitutional goals serve as the foundation for every judge’s decision. Such decisions not only aim to achieve lasting peace and justice for the parties involved but also for society at large or the majority of the Muslim community in Indonesia. Therefore, interfaith marriages between Muslim women and non-Muslim men should not be permitted. Furthermore, according to Constitutional Court Decision Number 68/PUU-XII/2014, which states that interfaith marriages are closely related to religion, the authority to resolve interfaith marriage cases should be held by Religious Courts. This is in line with Article 49 of Law Number 3 of 2006 on Religious Courts, which specifies one of their authorities is related to marriage matters.